Famine and dust : Dust Bowl - Loh-Hagan, Virginia (Loh-Hagan, Virginia. Behind the curtain., 2019)
Presents a reader's theater text to help students see different sides of the Dust Bowl including the view from a government journalist, the view of an Oklahoma farmer, and the view of a migrant farm worker. Includes a glossary, sidebars with more information, and resources for further study.